NON-COMPACTION MYOCARDIUM OF THE LEFT VENTRICLE: SECONDARY PREVENTION OF THROMBOEMBOLISM - R. P. Myasnikov; О. V. Kulikova; М. S. Kharlap; S. N. Koretsky; Е. Yu. Andreenko; E. A. Mershina; V. Е. Sinitsin; S. А. Boytsov (Кардиоваскулярная терапия и профилактика, 2017)
Main clinical specifics  of  the  non-compaction   myocardium  of  left ventricle (NCM) are heart  failure, arrhythmias and thromboembolism. Severe trabecularity and deep intertrabecular spaces might be the origin of blood congestion and formation of clots inside the left ventricle (LV). The article focuses on the recent aspects of anticoagulation in NCM, and presents clinical case of man 54 year old with NCM diagnosis, admitted with symptoms of severe heart failure and multiple clots in LV, complicated with repeat systemic embolism. Later, after patient’s voluntarily decrease of treatment,  repeat  thrombosis of the LV developed,  with embolism in the left brachial and in popliteal arteries.  All patients  with NCM, as asecondary prevention of thromboembolism, a permanent anticoagulation is indicated. Also, as a primary prevention, anticoagulation is needed for NCM patients  who need  thromboembolism risk factors,  such as atrial fibrillation and systolic dysfunction of the LV.